2016
DOI: 10.1016/j.foodchem.2016.02.139
|View full text |Cite
|
Sign up to set email alerts
|

Cationic beta-lactoglobulin nanoparticles as a bioavailability enhancer: Effect of surface properties and size on the transport and delivery in vitro

Abstract: BLG (beta-lactoglobulin) and CBLG (cationic BLG developed by our lab) were evaluated as potential nutraceutical/drug carriers. The cationic corona conferred CBLG with superior integrity and drug retention under gastrointestinal conditions, at most 40-fold higher mucoadhesion, up to 30-fold greater transepithelial permeation and, at most 285% higher cellular uptake, compared to BLG. Furthermore, the more hydrophilic CBLG species exhibited better mucoadhesion, while the more hydrophobic one exhibited higher cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
0
13
0
2
Order By: Relevance
“…Currently, developing an efficient method for drug delivery, such as nanoparticles, is crucial and urgent. It is proven that LG nanotransporters do not impair digestion; yet, it can successfully transport functional proteins and even enhance a compound's bioavailability [59, 60]. Our study directly demonstrated the mechanism of cellular LG transportation.…”
Section: Discussionmentioning
confidence: 58%
“…Currently, developing an efficient method for drug delivery, such as nanoparticles, is crucial and urgent. It is proven that LG nanotransporters do not impair digestion; yet, it can successfully transport functional proteins and even enhance a compound's bioavailability [59, 60]. Our study directly demonstrated the mechanism of cellular LG transportation.…”
Section: Discussionmentioning
confidence: 58%
“…Bovine β-lactoglobulin (BlgB) is a small protein (18.3 kDa) belonging to the lipocalin family. Due to BlgB ability to bind different classes of bioactive compounds, its application as a nutrients nanotransporter or drug carrier is currently an object of intensive studies [ 1 5 ]. Most of them are performed with commercially available natural lactoglobulin, but the use of recombinant protein seems to be a better alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, neutral and negatively charged emulsions undergo reversible depletion flocculation whereas cationic emulsions show irreversible associative electrostatic interactions with mucin and salivary salts. Similarly, Teng et al (2016) found that cationic polymers interact readily with mucin and exhibited better mucoadhesion properties than unmodified BLG. Moreover, Singh and Ye (2013) showed depletion flocculation of a BLG-stabilized emulsion (20 wt% soybean oil, 1.0 wt% BLG) when mixed with an artificial saliva composition containing PGM.…”
Section: Mucin/saliva Interactions With Blg-stabilized Emulsionmentioning
confidence: 87%